The Effectiveness of TikTok as A Media for Enhancing English Speaking Skills: A Systematic Literature Review - Enggal Rininggayuh; Intan Ayu Septika Dewi; Laely Ngaenatul Wardah Isnaeni (Proceedings Series on Social Sciences & Humanities, 2024)
In a globalized era, the transformative impact of technology on language education, particularly through platforms like TikTok, has become increasingly significant. This systematic literature review aims to assess the effectiveness of TikTok as a medium for enhancing English speaking skills. Acknowledging the paradigm shift caused by digital communication tools, especially social media, this review addresses the existing gap in comprehensive research on TikTok's efficacy as an educational tool in the context of English language instruction. Driven by the increasing commonness of TikTok in daily communication and its potential for creating dynamic and interactive learning environments, this study critically examines the impact of TikTok on the development of students' language skills and proficiency. The study adopts a critical viewpoint to evaluate innovative approaches utilizing technology in language education, highlighting TikTok's effectiveness in English speaking skills. The findings aim to critically contribute valuable insights for educators, curriculum developers, and policymakers, challenging assumptions and providing nuanced perspectives on the implications of incorporating TikTok into English language education.